Development of banana plants by using micro propagation method on tissue culture and cost analysis: a research / Muhammad Kahfi Kasah - Kasah, Muhammad Kahfi (Faculty of Plantation and Agrotechnology, 2018)
At the present, everyone already know and very familiar with the banana fruit crops due to a good taste, delicious and the benefit of eating banana fruits. Bananas are traditionally propagated using suckers which can be exposed by any disease such as panama disease, fusarium wilt, and sigatokadisease. It also affects the uniformity and shows slow process in plant growth. Plant propagation through tissue culture is one of the methods that can solve these problems via shoot tip culture in glass jars technique by using MS medium supplement with appropriate concentration of Napthalene Acetic Acid (NAA) and Benzylaminopurine (BAP). MS medium supplemented with 5 μg/L BAP produced the highest number of shoot from explant, while number shoot multiplication was observed on medium without cytokinin. The number of shoots reacted for establishing and their survivability was higher with NAA. MS medium supplemented with 1 μg/L NAA created the highest number of root. Plantlets cultured on medium without cytokinin gave more roots in the rooting medium during root induction after multiplication process. Eventually, the most important thing was aseptic technique and skill to avoid the explant from contaminations. The cost of tissue culture banana plantlet produced was determined by calculate the production cost incurred and the number per plantlets produced.